Socio-community inclusion and collective occupations: Dialogues between the institutional world and that of organizations of people with psychosocial disabilities - Vera Angulo, Rodrigo Javier.; Parra Molina, Valeria Alicia.; Sepúlveda Carrasco, Cristóbal Rodrigo. (Universidade Federal de Sao Carlos, 2022)
The article analyzes socio-community inclusion practices of groups of people with psychosocial disabilities, generated in doing and feeling in their collective occupations, from the dialogues that take place with social institutions. A qualitative methodology was used, with a critical approach. The information was collected through discussion groups, which made it possible to collect speeches from the participants of two groups of people with mental disabilities, corresponding to the communes of Penco and Concepción, in the Biobío Region (Chile); discourses that were coded, analyzed, categorized and interpreted. Among the most relevant results obtained, differences and tensions are evident in the ways of understanding and proceeding towards inclusion, since institutions tend to maintain hierarchical relationships, while groups tend to have more democratic and participatory practices. Regarding the conclusions, it is possible to visualize that the human rights of people with mental disabilities are materialized in a field of collective occupations, daily actions in everyday contexts, and social conflict.
Inclusão sócio-comunitária e ocupações coletivas: Diálogos entre o mundo institucional e o das organizações de pessoas com deficiência psicosocial
Inclusión sociocomunitaria y ocupaciones colectivas: Diálogos entre el mundo institucional y el de las organizaciones de personas con discapacidad psicosocial
Keywords: Terapia ocupacional; Intellectual disability; Integración social